A comparative dosimetric study comparing dose to the carotid artery using 3D conformal radiotherapy and intensity-modulated radiotherapy for T1-T2 glottic cancer at Gharbia Cancer Society, Egypt. Issue 2 (15th February 2017) - Mahmoud, Mohamed; Elfaramawy, Safa; Mokhtar, Maha H.
Abstract: Purpose: This is a dosimetric study to compare the feasibility of carotid artery sparing as a primary objective, as well as planning target volume coverage and dose to spinal cord as a secondary objective, by using 3D conformal radiotherapy (3DCRT) and intensity-modulated radiotherapy (IMRT) for patients with early glottis cancer. Patients and methods: Six patients who had been treated for early stage glottic carcinoma (stage T1-2 N0M0) were included in this study. All patients were immobilised in the supine position with a thermoplastic mask and treatment planning computed tomography scans were obtained from the top of the skull to the top of aortic arch with a 3-mm slice thickness. Two plans were created for every patient, one using 3DCRT and the second using IMRT. Comparison between the two plans was undertaken and analysis was made regarding the dose to the carotids arteries, target coverage and doses to the organs at risk. Results: For target coverage, the V 95% for both plans was the same with no significant difference, hot spots were the highest in 3DCRT with p =0·002, the homogeneity index for IMRT plan was better than 3DCRT ( p =0·0001). Regarding the dose to the carotids, it was significantly lower in the IMRT plan compared with the 3DCRT plan ( p =0·01). The spinal cord dose was significantly higher in the IMRT plan. Conclusion: IMRT significantly reduces the radiation dose to the carotid arteries compared with 3DCRT while maintaining clinical target volume coverage. Such a results assists in decreasing the incidence of radiation-induced carotid stenosis, thus improving the quality of life for patients.